148k views
0 votes
Factor – 1/2 out of -1/2x+6

What is the factored expression of this

User Troll
by
5.7k points

2 Answers

6 votes

Answer:
-(1)/(2)(x-12)

==================================================

Step-by-step explanation:

The terms of
-(1)/(2)x+6 are
-(1)/(2)x and
6

Divide each term by -1/2 to factor out the -1/2

If we divide
-(1)/(2)x over -1/2, then we'll get x. Basically the -1/2 terms cancel.

If we divide 6 over -1/2, we get -12. It might help to think of it as 6/(-0.5) = -12.

So overall we have
-(1)/(2)x+6 = -(1)/(2)(x-12)

You can use the distribution property to check the answer.

User Nasly
by
5.4k points
3 votes

Answer:

-1/2(x-12)

Step-by-step explanation:

Since you need to factor -1/2 out of the given expression, you can say that

-1/2x+6 is equal to

-1/2(x-12)

User Sonic Master
by
5.5k points